2006
DOI: 10.1080/00343400600757635
|View full text |Cite
|
Sign up to set email alerts
|

Why do disability benefit rolls vary between regions? A review of the evidence from the USA and the UK

Abstract: McVicar D. (2006) Why do disability benefit rolls vary between regions? A review of the evidence from the USA and the UK, Regional Studies 40, 519-533. Over the last 30 years, many Organization for Economic Co-operation and Development (OECD) countries have seen a dramatic rise in the share of the working-age population receiving earnings replacement sickness and disability benefits. The reasons behind this growth - particularly for the USA, but also to a lesser extent elsewhere - have been extensively researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 4 publications
3
47
0
Order By: Relevance
“…Our starting point is the idea that such programmes have been used to cushion recessions and to alleviate transitions into and from economic inactivity in regions of high unemployment, as suggested by a variety of studies including Beale and Nethercott (1988), Beatty and Fothergill (1996), Black, Daniel and Sanders (2002), Webb (1991), andMcVicar (2006). In addition, disability programmes have often been used as an alternative to early retirement through pension programmes, either because of restrictions on early retirement through conventional pension plans, or because disability programmes offer more attractive benefit levels or tax treatment of retirement benefits (Blöndal and Scarpetta, 1999;Gruber and Kubik, 1997;Wise, 1999, 2004;Haveman and Wolfe, 1984;Haveman, de Jong and Wolfe, 1991;Jiménez-Martin et al, 2006, Jiménez-Martin and Vall, 2009, and Riphahn, 1997.…”
Section: Disability Programmes and The Business Cyclementioning
confidence: 99%
“…Our starting point is the idea that such programmes have been used to cushion recessions and to alleviate transitions into and from economic inactivity in regions of high unemployment, as suggested by a variety of studies including Beale and Nethercott (1988), Beatty and Fothergill (1996), Black, Daniel and Sanders (2002), Webb (1991), andMcVicar (2006). In addition, disability programmes have often been used as an alternative to early retirement through pension programmes, either because of restrictions on early retirement through conventional pension plans, or because disability programmes offer more attractive benefit levels or tax treatment of retirement benefits (Blöndal and Scarpetta, 1999;Gruber and Kubik, 1997;Wise, 1999, 2004;Haveman and Wolfe, 1984;Haveman, de Jong and Wolfe, 1991;Jiménez-Martin et al, 2006, Jiménez-Martin and Vall, 2009, and Riphahn, 1997.…”
Section: Disability Programmes and The Business Cyclementioning
confidence: 99%
“…Previous research has shown that the risk of disability retirement varies by characteristics such as age and gender (5,6) as well as occupational class and various work-related factors (7,8). However, remarkably little attention has been paid to differences between geographical areas, even if large variation has been described between regional entities such as provinces or counties and between urban and rural municipalities (9,10). For instance, between Finnish counties the proportion of disability pension recipients of the population aged 16-64 years varied from 4.6 to 11.0%, while the average was 7.3%.…”
mentioning
confidence: 99%
“…In the US, for example, the southern states generally have a higher proportion of the working age population receiving Disability Insurance (DI) than other states (e.g. see Rupp and Stapleton, 1998;McVicar, 2006). Regional differences in Britain are particularly pronounced, with Wales and the North having considerably higher IB rolls than the South (e.g.…”
Section: Introductionmentioning
confidence: 99%